(untitled) - Harold E Doweiko (Belmont, California, 1990)
This book shatters myths, misconceptions, and misinformation about drugs of all types and offers straightforward information on what can be done help victimes of drug abuse or addiction. Topics covered include Alcoholics Anomynous, family intervention sessions, the " Minnesota Model " of chemical depency treatment, methadone maintenance, halfway house programs, ...
Keywords: substance abuse